Corporate Fraud: Causes, Effects, and Deterrence on Financial Institutions in Ghana - Osei-Assibey Mandella Bonsu; Li Kao Dui; Zou Muyun; Evans Kwabena Asare; Isaac Adu Amankwaa (European Scientific Journal, ESJ, 2018)
This paper focuses on finding the causes, effects, and deterrence and prevention of corporate fraud in the financial institution of Ghana. In particular, we examine the effects of fraud on a firm’s financial performance. A cross sectional model was used to find the effects of financial institutions fraud on financial performance. It was revealed that fraud has a significant negative effects on financial performance i.e. Return on Assets of financial institutions in Ghana. However, structured questionnaires were also used to find out the perception of Accountants, Auditors, and management on the main causes of banking fraud and deterrence and prevention methods in curbing the menace. It was revealed that weaker internal control, inadequate training and fraud policies, failed documents, and proper remuneration are the strong arsenal that causes fraud in financial institutions of Ghana. Moreover, organizational use of password protection, good remuneration, employee’s background checks, and adequate fraud training were perceived as the most deterrence and prevention method in fighting fraud in financial institutions. Our results have practical implication for management, accountants, auditors, and all stakeholders in financial institutions on the effects of fraud on firms financial performance and in mounting fool proof methods in curbing this canker and reducing it to its bearest minimum. The study contributes deterrence and prevention methods aimed at improving its effectiveness in reducing fraud in Ghana and West Africa.